Ecological rehabilitation of the River System of Dehradun City: A Multidimensional Approach - Prateek Dhasmana, Parminder Kaur, Kritika (International Journal of Advanced Science and Technology, 2020)
The rivers of Dehradun city are facing massive pressure due to anthropogenic activities. Dehradun city is growing in a uni direction since 1988 and due to extensive urbanization there is a lot of pressure on the hydrological system of the city. Water bodies are facing issues like encroachments, illegal mining, pollution and channelizing which had ecologically degraded these water bodies. River front development projects were introduced that are not problem solving as they in turn are channelizing the rivers thus depleting its natural ecology and biodiversity. The presence of invasive species found in the rivers are a proof of increasing anthropogenic activities. These water bodies are slowly loosing their biodiversity and majorly in the urbanized areas.This study worked on more of an ecological approach where the ecology of these water bodies is given top priority. Taken different models used around the globe, only those examples were considered which were more into deep ecology rather than anthropogenic in nature. With the help of research couple of river system models were developed which promotes ecological well being of these water bodies. The study gives an ecological path for the effective revival of the water bodies of Dehradun city.